Successful Insurgency: A Case Study of the Taliban Insurgency and Its Success in the Afghan War in 2021 - Muhammad Izzu Saukani (Dauliyah: Journal of Islam and International Affairs, 2024)
This article will try to analyze the strategy played by the Taliban insurgency group in the success of winning its insurgency in the Afghan conflict against the government and its international coalition, namely the US. The results of the study show that the success of the Taliban in winning the Afghan conflict is inseparable from the Taliban's ability to integrate various strategic instruments both military and non-military forces to support its insurgency. In this case, besides relying on military power, the Taliban cleverly launched a softer strategy (soft power) both by means of diplomacy, the use of social media to conduct propaganda and other softer ways. All of this was attempted for no other reason than to seek support for the legitimacy of the Taliban's insurgency movement. Keywords: Strategy, Soft power, Insurgency, Taliban, Afghanistan.